Comparison of the pharmacokinetic and pharmacodynamic profiles of insulin degludec and insulin glargine. (August 2015) - Heise, Tim; Hövelmann, Ulrike; Nosek, Leszek; Hermanski, Lidia; Bøttcher, Susanne G; Haahr, Hanne
<x xml:space="preserve">Abstract</x> Objectives: A medical need remains for a once-daily insulin with 24-h basal coverage in all patients. We characterize the steady-state (SS) pharmacokinetic/pharmacodynamic properties of insulin degludec (IDeg) versus insulin glargine (IGlar). Research design and methods: In this controlled, single-center study, 66 type 1 diabetes patients were randomized to two 8-day periods of once-daily IDeg or IGlar at 0.4, 0.6 or 0.8 U/kg. At SS, subjects underwent a 42-h euglycemic glucose clamp (5.5 mmol/l; 100 mg/dl). Glucose infusion rate (GIR), distribution of GIR and half-life were assessed. Results: Mean 24-h GIR profiles were flatter and more stable for all doses of IDeg versus IGlar. The evenly distributed glucose-lowering effect of IDeg was confirmed by the AUCGIR across one dosing interval, as each of the four 6-h intervals across one dosing interval contributed ∼ 25% of the AUCGIR, τ, SS. IGlar was most effective during the first 12 – 18 h after dosing. At SS, the half-life was 25.4 (IDeg) versus 12.1 h (IGlar). No safety concerns were identified for IDeg or IGlar. Conclusion: IDeg has a longer half-life (> 25 h) than IGlar. Exposure and glucose-lowering effects are more stable and evenly distributed across one dosing interval for IDeg versus IGlar (Clinical trials.gov identifier: NCT01114542).